Lactation Reduces Glial Activation Induced by Excitotoxicity in the Rat Hippocampus. (27th May 2013) - Cabrera, V.; Ramos, E.; González‐Arenas, A.; Cerbón, M.; Camacho‐Arroyo, I.; Morales, T.
<x xml:space="preserve">Abstract</x> Motherhood induces a series of adaptations in the physiology of the female, including an increase of maternal brain plasticity and a reduction of cell damage in the hippocampus caused by kainic acid (KA) excitotoxicity. We analysed the role of lactation in glial activation in the hippocampal fields of virgin and lactating rats after i.c.v. application of 100 ng of KA. Immunohistochemical analysis for glial fibrillary acidic protein (GFAP) and ionised calcium binding adaptor molecule 1 (Iba‐1), which are markers for astrocytes and microglial cell‐surface proteins, respectively, revealed differential cellular responses to KA in lactating and virgin rats. A significant astrocyte and microglial response in hippocampal areas of virgin rats was observed 24 h and 72 h after KA. By contrast, no increase in either GFAP‐ or Iba‐1‐positive cells was observed in response to KA in the hippocampus of lactating rats. Western blot analysis of GFAP showed an initial decrease at 24 h after KA treatment, with an increase at 72 h in the whole hippocampus of virgin but not of lactating rats. The number of GFAP‐positive cells was increased by lactation in the dentate gyrus of the hippocampus but not in CA1 and CA3 areas. The present results indicate that lactating rats exhibit diminished responses of astrocyte and microglial cells in the hippocampus to damage induced by KA, supporting the notion that the maternal hippocampus is resistant to excitotoxic insults.